Repair of Cast Partial Denture Made Easy– An Alternative Approach (Indian Journal of Public Health Research & Development, 2020)
Patients wearing cast partial denture might face breakage of denture due to any reasons. The ideal approach for repair of broken cast partial is electrosoldering. This paper presents an alternative approach for repair of cast partial denture using heat cure acrylic resin.
Keywords: Repair of denture, Electrosoldering, Cast Partial Denture.